Identifying challenges to critical incident decision-making through a macro-, meso-, and micro- lens: A systematic synthesis and holistic narrative analysis - May, Brandon; Milne, Rebecca; Shawyer, Andrea; Meenaghan, Amy; Ribbers, Eva; Dalton, Gary (Frontiers in Psychology, 2023)
It is predicted that emergency responses to critical incidents will increase over the next few decades, as society faces unique and dynamic challenges (e.g., pandemics, migrant crises, and terrorism). As such, it is necessary to breakdown, identify, and evaluate the unique barriers associated with decision-making in the context of critical incident responses. The aim of the current study was to synthesize the bibliographic characteristics of the research on decision making and present a holistic narrative analysis of the multi-layered factors. Additionally, the systematic synthesis of evidence facilitated a critical appraisal of the quality and distribution of evidence across macro-, meso-, and micro- levels. Results suggested that research was moderately heterogeneous, as evidence captured diverse narrative factors. However, micro-centric characteristics (e.g., cognitive-related factors) were not well represented. Instead, research primarily focused toward intermediate meso-level characteristics, capturing factors such as “interoperability” and “organization policy and procedure” as critical challenges to decision-making. Six key narratives were also identified and discussed. Both the quality appraisal and narrative findings suggested that research should seek opportunities to experimentally assess, evaluate and validate decision-making. Whilst this has previously appeared ethically and practically problematic, advances in technology, research and analysis have allowed high-fidelity simulation experimentation to recreate critical incidents.